Integrity of welded joints made of alloy NiCr21Mo - Filip Vučetić; Branislav Đorđević; Mihajlo Aranđelović; Simon Sedmak; Nenad Milošević; Dorin Radu; Lazar Jeremić (Structural Integrity and Life Journal, 2023)
The research covers the investigation of mechanical properties of welded joint made on NiCr21Mo alloy (commercial trademark Incoloy 825), and joints of steels P355GH and X2CrNiMo17-12-2, as well as the influence of the achieved mechanical properties on structural integrity. Ongoing research is oriented on welded joints made of NiCr21Mo, i.e., the alloy to be introduced for certain parts (made of the aforementioned materials P355GH and X2CrNiMo17-12-2) of processing equipment exposed to elevated temperatures and high corrosive environment. Three preliminary welding technologies are presented in the first part of the paper. Tungsten inert gas (TIG) welding technique is used due to the type of filler material. The filler material features mechanical properties that provide an overmatching effect. After non-destructive tests (NDT), mechanical properties of all three welded joints are examined according to criteria that guarantee safe work and welded component integrity. In addition to mechanical tests (uniaxial tension, bending, impact toughness, hardness measurements), a microstructural analysis is performed to verify the applied preliminary welding technologies and evaluate the integrity of the obtained joints. After analysing all tests it is confirmed that the application of the preliminary welding technology has met all the requirements according to the applied criteria.
Keywords: welding; structural integrity; mechanical testing